THE CREATIVE WORK OF SHAROF RASHIDOV - Sulaymanova Shokhsanam Absamatovna (Bright Mind Publishing, 2026)
This article examines the creative work of the renowned statesman Sharof Rashidov. Specifically, the article analyzes the multifaceted creative work of the writer and statesman based on various historical sources.
Keywords: Eastern literature, artistic creativity, literature, politics, head of state, creative examples